Synthesis of Novel 1,4- Dihydropyridine Derivatives Bearing Biphenyl-2'-Tetrazole Substitution as Potential Dual Angiotensin II Receptors and Calcium Channel Blockers - Javid Shahbazi Mojarrad; Zahra Zamani; Hossein Nazemiyeh; Saeed Ghasemi; Davoud Asgari (Tabriz University of Medical Sciences, 2011)
Introduction: We report the synthesis of novel 1,4-dihydropyridine derivatives containing biphenyl-2'-tetrazole moieties. We hypothesized that merging the key structural elements present in an AT1 receptor antagonist with key structural elements in 1,4-dihydropyridine calcium channel blockers would yield novel analogs with potential dual activity for both receptors. This strategy led to the design and synthesis of dialkyl 1,4-dihydro-2,6-dimethyl-4-[2-n-alkyl-1-[2΄-(1H-tetrazole-5-yl) biphenyl -4-yl] methyl] imidazole-4(or 5)-yl]- 3, 5-pyridinedicarboxylate analogs. Methods: These compounds were obtained by two methods starting from biphenyltetrazolyl-4-(or 5)-imidazolecarboxaldehyde intermediates employing in classical Hantzsch condensation reaction. In the first method, triphenylmethyl protecting group of 4- or 5-carboxaldehyde intermediate was first removed in acidic media and then classical Hantzsch reaction was employed in order to obtain the final products. In the second method, without further deprotection process, protected 4- or 5-carboxaldehyde intermediate directly was used in Hantzsch reaction. Results: The second method was more efficient than the first method since the deprotection and ring closure reaction occurs simultaneously in one pot. Conclusion: Eight novel dihydropridines analogs were synthesized using classic Hantzsch condensation reaction. Chemical structures of the compounds were characterized by 1H NMR, infrared and mass spectroscopy.